2015
DOI: 10.1002/app.42197
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the influences of the pellet shape on the bulk density and the frictional behavior of polypropylene

Abstract: Bulk solids are the raw material for almost every polymeric thermoplastic product. Their properties determine the quality of solids conveying and also influence the melting behavior of the material in processing units. This study investigates the influence of pressure and temperature on the bulk density of two thermoplastic polypropylene pellets of different shapes. Furthermore, the external friction dependent on temperature and pressure of those materials is examined at conditions usually occurring in the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It has been figured out that cylindrical pellets caused a much higher throughput than spheroidal ones. A further work indicates that possible reasons for that are the higher bulk density which can be explained by a higher packing density and a higher coefficient of friction [15]. In this studied case the solids conveying zone mainly determines the throughput of the extruder.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…It has been figured out that cylindrical pellets caused a much higher throughput than spheroidal ones. A further work indicates that possible reasons for that are the higher bulk density which can be explained by a higher packing density and a higher coefficient of friction [15]. In this studied case the solids conveying zone mainly determines the throughput of the extruder.…”
Section: Introductionmentioning
confidence: 75%
“…The measurements of the bulk density at increased pressure and temperature [15] have shown that the bulk density of cylindrical pellets strongly increases with higher pressure, especially at higher temperature. Figure 2 (a) shows that the measured bulk density of the cylindrical bulk reaches or exceeds that of the spheroidal bulk at 120 °C and pressures above 20 bar (2 MPa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modelling of these extruders is commonly subdivided into functional zones, which are the hopper, the flow-in zone, the solids conveying zone, the delay zone, the melting zone, and the metering zone. In some cases, additional mixing and degassing zones are used [1][2][3][4][5][6][7][8][9]. The throughput, the quality, and the homogeneity of the processed material are strongly influenced by the melting performance of SSE.…”
Section: Introductionmentioning
confidence: 99%
“…During melting more polymer melt penetrates into the free space between spheroidal pellets compared to cylindrical ones (Kneidinger et al [42]). In addition, cylindrical shaped bulk solids exhibit a higher external coefficient of friction compared to spheroidal ones, which boosts the solid conveying behavior and increases the extruder output (Längauer et al [8,9]). The coefficient of friction of mixtures of different polymers of investigated by Shim [43].…”
Section: Introductionmentioning
confidence: 99%